Poblaciones de acaros en la cubierta vegetal de huertos de manzanos - Costa-Comelles, J.=700 1 Santamaria, A.; Ferragut, F.; Garcia-Mari, F.
(Es, En)
ilus., 9 ref.
Keywords: HUERTO FRUTAL; MANZANA; CUBIERTA VEGETAL; POTENTILLA; RUMEX; TRIFOLIUM PRATENSE; ACAROS NOCIVOS; CONTROL BIOLOGICO; ESPAÑA; FITOSEIDOS TETRANIQUIDOS